If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 8 * -3 + b Multiply 8 * -3 -2 = -24 + b Solving -2 = -24 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -2 + -1b = -24 + b + -1b Combine like terms: b + -1b = 0 -2 + -1b = -24 + 0 -2 + -1b = -24 Add '2' to each side of the equation. -2 + 2 + -1b = -24 + 2 Combine like terms: -2 + 2 = 0 0 + -1b = -24 + 2 -1b = -24 + 2 Combine like terms: -24 + 2 = -22 -1b = -22 Divide each side by '-1'. b = 22 Simplifying b = 22
| -2(3x+5)-6(x)= | | (-6x^2)+8x=0 | | -325=13x | | 5r^2=-32+28r | | 4=2.5x | | -5n+5+3n=-15 | | 6m+6=10m+24 | | f(1)=5-2(1) | | 7(4-9)=-26+6x | | 5(x+43)+-2=-2 | | -14+9x=11+8x | | (X*5)-16=3(X+10) | | (4x^2-6x+8)+(7x-3)=0 | | 4.2x-1.5=1.9x+7.7 | | -4(x+12)+9=-7 | | 16*x=64 | | p(x)=x^4-3x^3+18x^2-48x+32 | | -53-7x=55+2x | | 2x-39+-4x=3 | | 4t-5t=3 | | -42+9x=x+86 | | 4x+19=83 | | 5u-6=-21 | | 3(x+41)+8=50 | | 3.8r=-6 | | -29+6x=31+11x | | -2x-47+4x=-21 | | (x+14)(x-2)= | | 10x-45+12x=43 | | 3r(4r-5)=6(5r+8) | | -3y+10x=-5 | | P=11*3 |